Molecular docking based inhibition of Trypanothione reductase activity by Taxifolin novel target for antileishmanial activity - Ravi Kumar Gundampati and Medicherla V. Jagannadham (Journal of Applied Pharmaceutical Science)
The theoretical docking study, conducted on a sample of previously reported for anti-inflammatory and antioxidant activities of Taxifolin at the binding site of Leishmania infantum trypanothione reductase (Try R) examine interaction energy. Taxifolin is widely used in the traditional medicine have been investigated for their putative chemo preventive and antileishmanial properties for the last few decades. A theoretical docking study, the evaluation of Taxifolin as inhibitor of trypanothione reductase a validated drug target enzyme of the Leishmania parasite. Taxifolin was found to bind at active site of L. infantum TryR with lowest binding energy and RMSD values to be -8.82 Kcal/Mol and 2.0 Å respectively. Docking analysis of TryR with ligand enabled us to identify specific residues viz. Ser-14, Ala-47, Ser-162, Thr-336 and Arg-286, within the TryR binding pocket to play an important role in ligand binding affinity. The availability of TryR built model, together with insights gained from docking analysis will promote the rational design of potent and selective TryR inhibitor as antileishmanial therapeutic. The study contributes towards understanding mechanism of antileshmanial effect of the Taxifolin. This compound has shown promising biological activity in preliminary studies by targeting multiple signaling pathways. Thus on the basis of our in silico studies we hypothesize that this compound into Taxifolin can be inhibitory effect on against leishmaniasis.
Keywords: Autodock, Trypanothione reductase, Taxifolin, Leishmania infantum, antileishmanial activity, eishmaniasis.